Peranan Purchasing Departement Dalam Operational In Hotels - Nugraha, Rizki Nurul; Utami, Dinda Novanda; Salim Zuhdi, Muhammad; Kahla, Hanifa Fahri Fadhilla; Rizal, Arsyeaf (Jurnal Ilmiah Wahana Pendidikan, 2023)
Hotel is a form of building, symbol, company or accommodation business entity that provides lodging services, food and beverage providers and other service facilities where all of these services are intended for the general public, both those who spend the night at the hotel or those who only use certain facilities. owned by the hotel. This study examines the role of the Purchasing Department in Operational In Hotels. The purpose of this study is to determine the important role of Purchasing between hotels and suppliers. Goods ordered from suppliers will receive several terms and conditions according to the information in the Purchase Order (PO). Purchasing will oversee the ongoing process of procurement of goods until the goods ordered arrive at the hotel. This research is presented qualitatively. The techniques used for data collection were observation, interviews, document studies, literature studies, internet searching. Based on the results obtained, the role of a Purchasing in In Hotel is very important, because everything relates to hotel needs. The results of the research show the steps or methods that are carried out by the purchasing party. How does the purchasing party meet the needs of goods from each department. Barriers experienced by Purchasing are related to the Daily Market List which causes delays in placing orders with suppliers. Experience and professionalism of a Purchasing, and dealing with all the problems encountered